2012
DOI: 10.1353/hpu.2012.0076
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Academic Partnership to Plan and Implement an Evidence-Based Lay Health Advisor Program for Promoting Breast Cancer Screening

Abstract: Despite a growing body of evidence concerning effective approaches to increasing breast cancer screening, the gap between research and practice continues. The North Carolina Breast Cancer Screening Program (NC-BCSP) is an example of an evidence-based intervention that uses trained lay health advisors (LHA) to promote breast cancer screening. Partnerships that link academic researchers knowledgeable about specific evidence-based programs with community-based practitioners offer a model for increasing their use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…These efforts originated through local community and academic partnerships and were supported by grants from foundations, the North Carolina Office of Minority Health and Health Disparities, and research programs such as the CCN [26]. Despite improvement among some measures in recent years, the apparent progress may be short-lived given the variation in findings among other measures and the declines in funding for community-based health promotion and prevention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts originated through local community and academic partnerships and were supported by grants from foundations, the North Carolina Office of Minority Health and Health Disparities, and research programs such as the CCN [26]. Despite improvement among some measures in recent years, the apparent progress may be short-lived given the variation in findings among other measures and the declines in funding for community-based health promotion and prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Among community efforts (see Table 1), a lay health advisor program—initiated in the early 2000s based in local beauty shops and more recently enhanced through grant funding [26]—has sought to overcome cultural barriers by providing information on breast cancer in general and increasing people’s awareness of breast cancer screening specifically, including by referring people to the health department and elsewhere for screening. Throughout the 2000s, several other efforts were funded by agencies like the North Carolina Office of Minority Health and Health Disparities, the Susan G. Komen Foundation, and even the CCN, and the community was introduced to new levels of detail regarding breast cancer, including the existence of different disease subtypes and AA women’s differential susceptibility to more aggressive subtypes like hormone receptor negative disease.…”
Section: Discussionmentioning
confidence: 99%
“…CPCRN researchers from Emory, UTH, Texas A&M, UCLA, and USC have instituted minigrant programs (ranging from $3,500–$12,000/participating organization) as another approach to supporting CBOs’ implementation of specific EBIs that have proven to be effective at changing diet, physical activity, and screening behaviors (37, 39, 42, 43). The training and technical assistance offered typically focused on several of the GTO steps, including goal setting, addressing capacity, planning, implementing, and evaluating.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown the usefulness of training community health advisors to provide psychosocial support and act as a liaison between clinicians and individuals they seek to serve [25][26][27]. By sharing similar cultural, social and economic characteristics as the populations of interest, they are more inclined to connect and understand the subtle distinctions that influence health behaviors [26].…”
Section: Discussionmentioning
confidence: 99%